Transitions in water harvesting practices in Jordan's rainfed agricultural systems: Systemic problems and blocking mechanisms in an emerging technological innovation system. Issue 84 (June 2018) - Sixt, Gregory N.; Klerkx, Laurens; Griffin, Timothy S.
Highlights: We analyze system barriers for water harvesting innovation in Jordanian agriculture. We utilize functional-structural technological innovation systems analysis. Main barriers are financial limitations, lack of a common vision, and institutional. We suggest policy interventions to build protected niches and increase coordination. Foreign donors and traditional law play large role in developing country transition. Abstract: This study identifies systemic problems and opportunities for transitions in water harvesting − a water conserving agricultural practice − in the context of a developing country pursuing greater agricultural sustainability. We utilize a combined and enriched functional-structural technological innovation system (TIS) analysis to identify systemic problems in the water harvesting TIS in rainfed agricultural production systems of Jordan. Results indicate Jordanian water harvesting TIS development is hindered by three principal blocking mechanisms: 1) inadequate financial resources to support innovation; 2) lack of a common vision across government ministries; 3) institutional problems that inhibit legitimizing the technology. These challenges are caused by interlocking systemic problems, which indicate the need for integrated policy approaches and interventions. Our analysis reinforces the concept that in developing countries, donor interventions should be centrally considered because they play a role in influencing priorities throughout the system and in supporting TIS development. Donors can counteract TIS development and contribute to directionality problems that favor one form of the technology over another, which gives insufficient protection for the water harvesting TIS until markets for technologies form. This would require more effective coordination between different donors' efforts to develop critical mass in TIS development. We also show that cultural institutions and interactions between formal and informal land tenure laws play a significant role in causing an erosion of trust in the government and counter efforts to promote and engage farming communities in water harvesting activities and innovation. This requires recognition that, in developing countries, informal institutions may have the same status as formal institutions.